Efficacy of argatroban plus alteplase according to time from onset to thrombolysis in acute ischemic stroke: a prespecified post-hoc analysis of the ARAIS trial - Cui, Yu; Wang, Er-Qiang; Wang, Yi-Han; Chen, Hui-Sheng (Frontiers in Neurology, 2025)
BackgroundThe Argatroban Plus Recombinant Tissue-Type Plasminogen Activator for AIS (ARAIS) trial failed to demonstrate the benefit of argatroban in patients diagnosed with acute ischemic stroke who were treated with intravenous alteplase. A post-hoc analysis was conducted to investigate whether the time from onset to thrombolysis (OTT) affected the outcomes.MethodsThe included patients were classified into two subgroups according to OTT. The primary outcome was an excellent functional outcome at 90 days, defined as a modified Rankin Scale score of 0 or 1. The efficacy of argatroban plus alteplase was investigated in each subgroup compared with alteplase alone.ResultsOverall, 696 patients were included: 452 were assigned to the OTT < 180 min subgroup, and 244 to the OTT ≥ 180 min subgroup. The treatment effect of argatroban plus alteplase was similar to that of alteplase alone in the OTT < 180 min subgroup (adjusted RD [95% CI] = 0.5% [−5.6 to 6.6%]) and OTT ≥ 180 min subgroup (adjusted RD [95% CI] = −1.3% [−9.8 to 7.1%]). No significant interaction between the treatment efficacy and OTT was found (p = 0.75).InterpretationThe prespecified secondary analysis indicated that the efficacy of argatroban plus alteplase did not differ according to OTT in terms of achieving 90-day excellent functional outcomes compared with alteplase alone.Trial registrationClinicalTrials.gov, Identifier: NCT03740958.